COMPARATIVE ANALYSIS OF WEIGHT AND COST INDICATIONS OF INDUCTION MOTORS WITH CYLINDRICAL AND AXIAL AIR GAPS - А.А. Stavinskii (National Technical University "Kharkiv Polytechnic Institute", 2015)
Purpose. To find the analytical expressions of determining the optimum geometric dimensions by criteria of the weight minimum and the cost minimum of axial field squirrel-cage induction motors and to compare traditional and axial field motors. Methodology. We have applied the adapted method of the relative indications of the technical level with relative controlled variables. We have used the approximation of the experimental dependence of the distribution of the induction in the air gap and the integral averaging of the electromagnetic characteristics. Results. We have developed the mathematical model for determining the optimum geometric dimensions by criteria of the weight minimum and the cost minimum of the active part of axial field squirrel-cage induction motors taking into account the radial distribution of the induction in the air gap and teeth. We have considered the comparative analysis of the indications of the weight and the cost of traditional and axial designs of electromagnetic equivalent motors. Originality. For the first time we have created the relative units mathematical model of the weight and the cost of the active part of axial field squirrel-cage induction motors with the uneven distribution of the magnetic flux in the core and investigated the effect of the geometric relationships on the materials consumption and cost of axial field motors. Practical value. Based on the superior parametric compatibility and the high material savings of axial motors the expediency of replacing traditional induction motors to axial field induction motors has been proved in the special transport drives. Also obtained by simulation optimal geometric relationships of the magnetic circuit can be used in the manufacture and design of axial motors by criteria of the weight minimum and the cost minimum.